2017
DOI: 10.1038/srep39684
|View full text |Cite
|
Sign up to set email alerts
|

miRsig: a consensus-based network inference methodology to identify pan-cancer miRNA-miRNA interaction signatures

Abstract: Decoding the patterns of miRNA regulation in diseases are important to properly realize its potential in diagnostic, prog- nostic, and therapeutic applications. Only a handful of studies computationally predict possible miRNA-miRNA interactions; hence, such interactions require a thorough investigation to understand their role in disease progression. In this paper, we design a novel computational pipeline to predict the common signature/core sets of miRNA-miRNA interactions for different diseases using network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Computational predictions and some experimental results have shown that miRNA cluster interactions do take place (Song et al, ). miRNA–miRNA interaction plays an important role in regulating various biological functions, and alterations are reported in many pathophysiological conditions (Cloonan, ; Nalluri et al, ). Deregulation of miRNA clusters can alter the cross talk between miRNA clusters (inter‐ and intra‐cluster interactions) as well as affecting target genes and associated signalling pathways, and can thereby greatly influence the pathophysiology of disease.…”
Section: Oncogenic and Tumour‐suppressor Mirna Clustersmentioning
confidence: 99%
“…Computational predictions and some experimental results have shown that miRNA cluster interactions do take place (Song et al, ). miRNA–miRNA interaction plays an important role in regulating various biological functions, and alterations are reported in many pathophysiological conditions (Cloonan, ; Nalluri et al, ). Deregulation of miRNA clusters can alter the cross talk between miRNA clusters (inter‐ and intra‐cluster interactions) as well as affecting target genes and associated signalling pathways, and can thereby greatly influence the pathophysiology of disease.…”
Section: Oncogenic and Tumour‐suppressor Mirna Clustersmentioning
confidence: 99%
“…The predicted gene interaction networks (or equivalently termed as gene coexpression networks in some cases) were built with miRsig [17]. This tool applies seven different network inference algorithms on the gene expression data that individually reverse-engineer the interaction scores between the genes.…”
Section: Network Analysismentioning
confidence: 99%
“…In this study, we identified the influential or causal genes using four RNA-Seq datasets from C.pseudotuberculosis, first by using the miRsigpipeline to obtain the predicted gene coexpression network [17] and next applying the miRinfluence tool to identify the influential and causal genes inside the network [15]. We adapted the methodology in these tools to determine the critical genes that play a causal role in the signaling cascade through influence diffusion and hence may regulate the overall gene expression of the entire network.…”
Section: Introductionmentioning
confidence: 99%
“…• EpimiR [36]: This data source contains the interactions and information between the epigenetic modification and miRNAs in the context of several diseases. It also provides information about the predicted transcription start cites which will help in providing more details in miRNA guided post-transcriptional gene regulation.…”
Section: Collated Databasementioning
confidence: 99%
“…The usage of network inference algorithms in the DREAM challenge, to reconstruct the gene-TF regulatory network [37] is a prime example. The prediction of disease specific miRNA-miRNA interaction network via a consensus-based network inference approach [36] is a recent example. Traditionally, these network inference algorithms have used experimentally available expression datasets as input to predict new associations based on the patterns of co-expression observed in the experiments.…”
Section: Algorithmsmentioning
confidence: 99%